Religion, Environmental Education, and Rewilding the Humanities - Berebon, Charles (Universitas Negeri Makassar, 2024)
The modern university often functions as an instrument of domestication, prioritizing the reinforcement of social and economic norms over the expansion of intellectual and imaginative frontiers. The Anthropocene epoch compels us to reimagine the humanities not as isolated, hierarchical disciplines but as foundational to understanding human existence and ethical responsibility within a more-than-human world. This essay advocates for restructuring the American academy in line with Mark C. Taylor’s vision of a multidisciplinary space dedicated to the “comparative analysis of common problems”. It proposes that religious traditions provide valuable frameworks for integrating the humanities (literature, philosophy, arts), social sciences (governance, law), and STEM fields. Furthermore, as society confronts unprecedented environmental, technological, and economic upheavals, engaging with religious texts becomes essential for critiquing the limitations of liberal ideologies ill-equipped to address the climate crisis. This paper introduces the concept of “rewilding” higher education, modeled after conservation principles, emphasizing three key tenets: creativity, curriculum, and collaboration. While focusing on the intersections of religion, ecology, and climate ethics, this approach has implications for all academic disciplines..